Environmental factors of motivation mechanism of employees' innovative activity in the enterprise - Bielova, O.I.; Бєлова, Олена Ігорівна (Центральноукраїнський національний технічний університе, 2021)
Every business operates in an environment. In general, the influence of the environment on the innovative activity of the enterprise determines its overall development, ensures the efficiency of its activities, and sometimes even determines the further path of its development. Therefore, the activities of each strategically oriented and innovatively active enterprise is impossible without the correct diagnosis of its condition and forecasting the development of the enterprise environment. The obtained results of diagnosing and forecasting serve as a basis for the formation of the company's mission, the choice of its goals and strategies, including innovative, as well as significantly affect the formation of an effective motivational mechanism and serve as a basis for its creation
Keywords: motivation employees' innovative activity